Jamaica. Significant Achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The main activities carried out by the Institute in Jamaica during 2019 are identified, with respect to the needs and interests of the country, strengthening issues of soil management, good agricultural practices, climate change, bioeconomy and health and food safety, through the support to the Codex Alimentarius Commission. Likewise, it contributed to the development of agrotourism, the contributions of the private sector with the public, the inclusion of young people in agricultural processes. Finally, work was done on pest control, such as citrus and cocoa diseases, as well as strengthening the cocoa production chain.